Penggunaan Media Pembelajaran Bahasa Arab Berbasis Video Untuk Meningkatkan Maharah Kalam Dalam Kitab Al-‘Arabiyyah Lin Nasyiin - Muhammad Nashrullah; Nur Halim; Rijalul Ghifari Al Fanani (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
This research is motivated by the difficulties of students in speaking skill learning which are influenced by several factors, namely students' internal factors, including low understanding and dismissive attitudes, and external factors in the form of teachers who are still not precise in choosing learning techniques or methods, as well as factors from schools, namely tools or learning media that are still not evenly distributed. Therefore, this study aims to describe how to apply the Kitab Al Arabiyyah Lin Nasyiin with a video-based learning media. This study uses a qualitative method, the data generated is not in the form of numbers. The results of this study are the use of video-based media is very interesting for students because the video is audio-visual.